What is the best initial treatment for an adult diagnosed with ADHD?. Issue 2 (February 2017) - de Mata, Jericho; Hassan, Yousif; Abbas, Ghulam
Abstract : EVIDENCE‐BASED ANSWER : Treatment with psychostimulant medications such as methylphenidate and amphetamine derivatives moderately improve short‐term symptom severity compared with placebo in adults with attention deficit hyperactivity disorder (ADHD) and should be used as initial pharmacological treatment (SOR: A, meta‐analyses of RCTs and evidence‐based guideline).